SEKOLAH TINGGI DESAIN KOMUNIKASI VISUAL DI KOTA PONTIANAK (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Over the recent years, the creative economy sectors has shown rapid growth thanks to the development of digital technology in 4.0 era. Visual Communication Design is one of those sectors mentioned above. It’s proven by variant opportunities and needs of professionals in design field and similar others. However, educational facilities that organizing and producing labor in Visual Communication Design is still unavailable in Pontianak. Pontianak, Capital of West Borneo/Kalimantan which is well known as central of west kalimantan’s populations’ activites is considered as a strategic location to establish higher educational facilities for Visual Communication Design sector. Academy of Visual Communication Design in Pontianak is a tertiary education institution that organizes education in design field by providing studies related to media and communication. (especially Visual Communication Design). Throughout the education program, the academy will produce professional labors with prospects of the world of work in the field of design including: graphic designers, multimedia, visual communication, product design, illustrator, photographers, animators, web designers in Pontianak. The planning stage of the Academy using J.C. Jones model which consists of concept, data collecting, analyze, synthesize, evaluation and optimalization. Those stages aims to produce a concept to build Academy of Visual Communication Design that will able to help the development of skills and creativities of it learners in order to increase human resource qualities in Pontianak.